The Influence of Motivation, Discipline, and School Environment on Students’ Academic Performance in the Implementation of the Merdeka Curriculum at SMKN - Sri Rejeki (Innovative Pedagogy and Education Studies, 2024)
This study aims to examine the influence of motivation, discipline, and school environment on students’ academic performance in the implementation of the Merdeka Curriculum at a vocational high school (SMKN). A quantitative research approach with a correlational design was employed. The population of this study consisted of all students at the selected SMKN, with a sample of 120 students determined using random sampling techniques. Data were collected through structured questionnaires using a Likert scale to measure motivation, discipline, and school environment, while students’ academic performance was obtained from academic records. The collected data were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results indicate that motivation, discipline, and school environment each have a significant positive effect on students’ academic performance. Furthermore, the simultaneous test shows that these three variables collectively contribute significantly to students’ academic achievement in the context of the Merdeka Curriculum implementation. These findings highlight the importance of strengthening students’ internal factors and creating a supportive school environment to optimize learning outcomes under the Merdeka Curriculum framework.